2022
DOI: 10.3389/fcell.2022.935363
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory-Metal Profile as a Hallmark for COVID-19 Severity During Pregnancy

Abstract: Pregnancy makes women more susceptible to infectious agents; however, available data on the effect of SARS-CoV-2 on pregnant women are limited. To date, inflammatory responses and changes in serum metal concentration have been reported in COVID-19 patients, but few associations between metal ions and cytokines have been described. The aim of this study was to evaluate correlations between inflammatory markers and serum metal ions in third-trimester pregnant women with varying COVID-19 disease severity. Patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 108 publications
0
2
0
Order By: Relevance
“…COVID-19 infection has a negative impact on the cytokine profile of pregnant women, varying according to the trimesters of pregnancy ( 18 ). Increased levels of cytokines, mainly proinflammatory cytokines, are correlated with the severity of the disease and predispose to miscarriage or premature birth ( 19 , 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 infection has a negative impact on the cytokine profile of pregnant women, varying according to the trimesters of pregnancy ( 18 ). Increased levels of cytokines, mainly proinflammatory cytokines, are correlated with the severity of the disease and predispose to miscarriage or premature birth ( 19 , 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…Pregnant women present changes in the immune system; therefore, they are generally considered vulnerable to infectious diseases [ 5 , 6 ]. Several studies have reported that pregnant women who experienced severe symptoms of COVID-19 were at higher risk for cesarean delivery, postpartum hemorrhage, hypertensive disorders of pregnancy, preterm birth, and maternal death [ 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%